Groundwater monitoring guidelines for the coal industry - Barnes, Michael Robert (University of the Free State, 2011)
Abstract not available
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2011
Keywords: Groundwater -- Sampling; Groundwater -- Quality; Groundwater -- Risk assessment